Development of Metacognitive Strategies in Early Childhood Education Learning for Improving Early Childhood Learning Independence in the Digital Era 2026 - Rabitah Hanum Hasibuan; Khoirotun Habiba; Duwi Wulandari; Lidiya Atmasari; Lena Salindi; Siti Ulia Nurhasanah (CV. Creative Tugu Pena, 2026)
This study aims to develop and examine the effectiveness of metacognitive strategies in Early Childhood Education (ECE) to enhance self-regulated learning (SRL) among children aged 4–6 years in the digital era of 2026. Digital technology has fundamentally transformed the early childhood learning landscape; however, this transformation has not been matched by adequate pedagogical strategies to cultivate independent learners from an early age. A metacognitive approach—encompassing children's ability to plan, monitor, and evaluate their own learning processes—is considered a strategic solution to address this challenge. This study employed a Research and Development (R&D) approach using the ADDIE model with a quasi-experimental design. The sample comprised 120 early childhood learners from 6 ECE institutions in Medan City, North Sumatra, selected through purposive cluster sampling. Data were gathered using structured observation instruments, an SRL scale, and in-depth interviews with teachers and parents. Results indicated that the application of technology-based metacognitive strategies significantly improved children's SRL scores by 38.7% (p < 0.001) compared to the control group. The self-monitoring dimension showed the highest improvement (42.3%), followed by independent planning (35.6%) and self-evaluation (38.1%). These findings suggest the necessity of regularly integrating metacognitive strategies into ECE curricula, particularly in addressing 21st-century competency demands and the artificial intelligence era.